Completeness of reporting and risks of overstating impact in cluster randomised trials: a systematic review. Issue 8 (August 2021) - Turner, Elizabeth L; Platt, Alyssa C; Gallis, John A; Tetreault, Kaitlin; Easter, Christina; McKenzie, Joanne E; Nash, Stephen; Forbes, Andrew B; Hemming, Karla; ,; Adrion, Christine; Akooji, Naseerah; et al.
Summary: Overstating the impact of interventions through incomplete or inaccurate reporting can lead to inappropriate scale-up of interventions with low impact. Accurate reporting of the impact of interventions is of great importance in global health research to protect scarce resources. In global health, the cluster randomised trial design is commonly used to evaluate complex, multicomponent interventions, and outcomes are often binary. Complete reporting of impact for binary outcomes means reporting both relative and absolute measures. We did a systematic review to assess reporting practices and potential to overstate impact in contemporary cluster randomised trials with binary primary outcome. We included all reports registered in the Cochrane Central Register of Controlled Trials of two-arm parallel cluster randomised trials with at least one binary primary outcome that were published in 2017. Of 73 cluster randomised trials, most (60 [82%]) showed incomplete reporting. Of 64 cluster randomised trials for which it was possible to evaluate, most (40 [63%]) reported results in such a way that impact could be overstated. Care is needed to report complete evidence of impact for the many interventions evaluated using the cluster randomised trial design worldwide.